IMPLICATURE IN MOVIE SCRIPT MUFASA THE LION KING (2024) - Ndruru, Asprilan; Silalahi, Charles David Marudut (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2025)
In "Mufasa: The Lion King" (2024), the screenplay skillfully utilizes implicature as a crucial element that enhances storytelling and adds depth to the emotional and thematic aspects of movie script. Implicature, a concept introduced by philosopher H. P. Grice, refers to the implied meanings that emerge in conversation, where speakers communicate ideas indirectly, relying on context and shared understanding between characters and the audience.This article delves into how the script of "Mufasa" employs both conversational and conventional implicatures to illuminate the intricacies of Mufasa’s character, particularly his relationships with his brother Scar and his son Simba, as well as broader themes of leadership, responsibility, and legacy. Through subtle and indirect communication, Mufasa conveys vital lessons while navigating his own internal and external conflicts, thus enriching the film's exploration of leadership and personal growth. By examining key dialogues and character interactions, this study underscores the significance of implicature in shaping the audience’s comprehension of character dynamics and the deeper meanings within the narrative. The use of implicature in "Mufasa" not only enhances character development but also engages viewers in an active process of interpretation, inviting them to read between the lines and discover the unspoken teachings woven throughout the dialogue.